Periodontal regenerative therapy in endo-periodontal lesions: a retrospective study over 5 years - Oh, Soram; Chung, Shin Hye; Han, Ji-Young (Journal of periodontal & implant science, 2019)
The aim of this study was to evaluate clinical and radiographic changes and the survival rate after periodontal surgery using deproteinized bovine bone mineral (DBBM) with 10% collagen or DBBM with a collagen membrane in endo-periodontal lesions. A total of 52 cases (41 patients) with at least 5 years of follow-up were included in this study. After scaling and root planing with or without endodontic treatment, periodontal regenerative procedures with DBBM with 10% collagen alone or DBBM with a collagen membrane were performed, yielding the DBBM + 10% collagen and DBBM + collagen membrane groups, respectively. Changes in clinical parameters including the plaque index, bleeding on probing, probing pocket depth, gingival recession, relative clinical attachment level, mobility, and radiographic bone gains were evaluated immediately before periodontal surgical procedures and at a 12-month follow-up. At the 12-month follow-up after regenerative procedures, improvements in clinical parameters and radiographic bone gains were observed in both treatment groups. The DBBM + 10% collagen group showed greater probing pocket depth reduction (4.52±1.06 mm) than the DBBM + collagen membrane group (4.04±0.82 mm). However, there were no significant differences between the groups. Additionally, the radiographic bone gain in the DBBM + 10% collagen group (5.15±1.54 mm) was comparable to that of the DBBM + collagen membrane group (5.35±1.84 mm). The 5-year survival rate of the teeth with endo-periodontal lesions after periodontal regenerative procedures was 92.31%. This study showed that regenerative procedures using DBBM with 10% collagen alone improved the clinical attachment level and radiographic bone level in endo-periodontal lesions. Successful maintenance of the results after regenerative procedures in endo-periodontal lesions can be obtained by repeated oral hygiene education within strict supportive periodontal treatment.